Uroflow measurement combined with electromyography testing of the pelvic floor in healthy children. Issue 1 (12th October 2018) - Samijn, Bieke; Van Laecke, Erik; Vande Walle, Johan; Pascal, Aurelie; Deschepper, Ellen; Renson, Catherine; Van den Broeck, Christine
Abstract : Aims: To investigate if the standard protocol for uroflowmetry, recommended by the International Children's Continence Society, remains accurate when integrating EMG measurement by means of superficial electrodes. Methods: A cross‐sectional study was conducted including healthy children. Group A performed two direct repetitions of uroflowmetry in combination with electromyography (uroflow/EMG). Group B performed a preceding measurement of isolated uroflowmetry, followed by two randomized measurements of uroflowmetry with and without EMG. Interpretation of uroflow curve was assessor blinded by a pediatric urologist and secondly performed using the flow index methodology. Statistical analysis compared different voids within each group and between group A and B. Results: Eighty‐three children were included and 206 uroflow measurements were obtained. In both groups statistical findings confirmed the hypothesis that it is preferable to perform an additional measurement before the use of uroflow/EMG. Although both groups showed improvement between voids, the group with initial uroflow measurement followed by uroflow/EMG measurement showed more improvement in concern of curve pattern. An initially better first void in group A, but no statistical difference between the second void in group A and uroflow/EMG testing in group B further demonstrates a higher improvement in group B. This suggests the use of a precedent uroflowmetry without EMG is preferable to immediate testing with EMG. Conclusions: It should be mandatory to perform one measurement in advance to ensure the reliability of the results. It is suggested to initiate the procedure with a single uroflowmetry measurement followed by one measurement of uroflow with EMG testing.